An aniline dication-like transition state in the Bamberger rearrangement - Yamabe, Shinichi; Zeng, Guixiang; Guan, Wei; Sakaki, Shigeyoshi (Beilstein Journal of Organic Chemistry, 2013)
A Bamberger rearrangement of N-phenylhydroxylamine, Ph–N(OH)H, to p-aminophenol was investigated by DFT calculations for the first time. The nitrenium ion, C6H5–NH+, suggested and seemingly established as an intermediate was calculated to be absent owing to the high nucleophilicity of the water cluster around it. First, a reaction of the monoprotonated system, Ph–N(OH)H + H3O+(H2O)n (n = 4 and 14) was examined. However, the rate-determining transition states involving proton transfers were calculated to have much larger activation energies than the experimental one. Second, a reaction of the diprotonated system, Ph–N(OH)H + (H3O+)2(H2O)13, was traced. An activation energy similar to the experimental one was obtained. A new mechanism of the rearrangement including the aniline dication-like transition state was proposed.
Keywords: Bamberger rearrangement; DFT calculations; N-phenylhydroxylamine; proton transfer; reactive intermediates; transition states